Un modelo de enfoque plurilingüe para la enseñanza de lenguas en la escuela - Martín Peris, Ernesto (Linguarum Arena, 2014)
The learning goals in the area of foreign language teaching in today’s world need to be defined anew, one of their main features being the giving up the construct of the native speaker as the paradigm of reference. It needs to be replaced by a set of the individual’s competences in different languages,that are variable and will have to be exercised in differentiated contexts and situations. The plurilingual approaches might be an appropriate response to these demands; taking as a starting point the concept of plurilingual competence, and building up on Cummins’ hypothesis of linguistic interdependence, a pedagogical model is put forward, that is being worked on for its later implementation in some different contexts of the language teaching in Spain. The model, which encompasses the whole of the languages repertoire of each individual learner, and aims at developing altogether the plurilingual competence and the intercultural awareness, will be tried out in a number of schools with different characteristics as to their educational level and sociopolitical context, and will be validated following the formative research methodology.